LEGAL PLURALISM AND COMMUNITY CHANGES: A REVIEW OF LEGAL PLURALISM INTEGRATION SYSTEM - Muhtamar, Syafruddin; Maskawati, Maskawati; Azikin, Arqam; M, Andriani; Moenta, A. Pangerang (Faculty of Law, Tanjungpura University, 2017)
The system of Eastern nations’ people lives is characteristic of Eastern cultures. Indonesia is a nation that also reflects these characteristics, in social and legal systems. Pre-colonization, the Indonesian people has been living in a pluralistic legal system, both in religious or customcharacterized systems. Until now, the both characteristic being a living law system inherited in history. The presence of colonization changed the model and the basic characteristics of the nation into a modern society with the west-styled colonial legal system. These western-modern systems continued post-independence and became the main pillar of development to change people lives. Therein the basic problem of the national legal system, that is legal pluralistic of society to be helpless in front of the hegemonic system of state law. Community changes in legal pluralism can occur if the contribution of living law systems (religion and customs) extends, without being sub-system or supporting or complementary of state law system. Hegemonic dominance of state law must continue to loosened, so that a free space of contribution for nation culturebased people legal system increasingly wider. Therefore, the legal pluralism integration system is important to establish in the national life. The paradigm of this system is a legal pluralism and its operation is integration of living law system with state law within the spirit and scope of legal pluralism. Thus, the purpose of this article are to analyze and determine the extent of relevance the concept of legal pluralism in the national development process concerned with a diversity of Indonesian culture.